Diuretic, natriuretic and potassium-sparing effect of nothofagin isolated from Leandra dasytricha (A. Gray) Cogn. leaves in normotensive and hypertensive rats. (25th April 2017) - de Almeida, Camila Leandra Bueno; Boeing, Thaise; Somensi, Lincon Bordignon; Steimbach, Viviane Miranda Bispo; da Silva, Luísa Mota; Andrade, Sérgio Faloni de; Delle Monache, Franco; Cechinel-Filho, Valdir; de Souza, Priscila
Abstract: Active constituents from natural origin have long been used for the treatment of patients suffering from cardiovascular and renal diseases. This study therefore aimed to investigate the diuretic and natriuretic properties of nothofagin, a dihydrochalcone isolated from Leandra dasytricha (A. Gray) Cogn. leaves in normotensive and hypertensive rats. Male Wistar normotensive rats were orally treated with vehicle (1 ml/kg); hydrochlorothiazide (HCTZ; 25 mg/kg); ethyl acetate fraction from L. dasytricha (EALD; 3–30 mg/kg) and nothofagin (NOT; 0.3–3 mg/kg). Spontaneously hypertensive rats (SHR) received NOT (1 mg/kg), HCTZ (25 mg/kg) or vehicle. The cumulative diuretic index, urinary electrolytes excretion (Na + and K + ), pH, density and conductivity were measured at the end of the experiment (after 8 h). A7r5 and L929 cell lines were used to measure cell viability after exposure to NOT. Nitric oxide generation was quantified in A7r5 cell supernatant, and DPPH assay was used for evaluating the antioxidant properties of NOT. The urinary volume of normotensive rats were increased after the treatment with EALD, without any changes in Na + or K + excretion. NOT was able to induce diuresis and natriuresis, but not kaliuresis, in both normotensive and hypertensive rats. The reduction in prostanoids generation through cyclooxygenase inhibition, as well as the muscarinic receptor antagonism, fully avoided NOT-induced increases in diuretic index. NOT, which did not interfere with L929 or A7r5 cell viability, was able to stimulate nitric oxide generation in A7r5 cell, besides showing an antioxidant effect in scavenging the free-radical DPPH. Taken together, our study shows, for the first time, the diuretic, natriuretic and potassium-sparing effect of nothofagin in rats, which was associated with prostanoids generation, muscarinic receptor activation and antioxidant properties. Graphical abstract: Highlights: Nothofagin isolated from L. dasytricha display diuretic and natriuretic effect. The diuretic effect is independent of an enhancement in potassium excretion. The mechanism of action may be due the ability of increase vasodilators mediators. This compound may be a candidate for the treatment of cardiovascular disorders.